2023
DOI: 10.2147/ndt.s439549
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Acute Kidney Injury in Intracerebral Hemorrhage Patients Using Machine Learning

Suhua She,
Yulong Shen,
Kun Luo
et al.

Abstract: Background: Acute kidney injury (AKI) is prevalent in patients with intracerebral hemorrhage (ICH) and is associated with mortality. This study aimed to verify the predictive accuracy of different machine learning algorithms for AKI in patients with ICH using a large dataset. Methods: A total of 1366 ICH patients received treatments between 2001 and 2012 from the Medical Information Mart for Intensive Care-III (MIMIC-III) database were identified based on the ICD-9 code: 431. The main outcome of AKI during hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Among these, antibiotics such as vancomycin and diuretics are frequently implicated. She et al utilized the random forest algorithm and found that vancomycin emerged as a significant predictive factor for AKI in patients with ICH ( 35 ). Additionally, another study noted that diuretic escalated the risk of AKI in individuals with acute stroke (OR = 8.5, 95%CI: 3.46–20.86, p < 0.001) ( 26 ).…”
Section: Non Hemodynamic Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, antibiotics such as vancomycin and diuretics are frequently implicated. She et al utilized the random forest algorithm and found that vancomycin emerged as a significant predictive factor for AKI in patients with ICH ( 35 ). Additionally, another study noted that diuretic escalated the risk of AKI in individuals with acute stroke (OR = 8.5, 95%CI: 3.46–20.86, p < 0.001) ( 26 ).…”
Section: Non Hemodynamic Mechanismsmentioning
confidence: 99%
“…Qureshi’s research indicated that patients with ICH who had a baseline blood creatinine level ≥ 110 μmol/L faced an elevated risk of AKI and renal adverse events, with OR of 2.4 (95%CI, 1.2–4.5) and 3.1 (95%CI, 1.2–8.1), respectively ( 4 ). A study involving 1,366 ICH patients similarly highlighted creatinine as a characteristic of AKI ( 35 ). However, some studies have found no correlation between renal function and AKI, and the presence of CKD alongside AKI did not correlate with long-term mortality (OR = 3.13, 95%CI: 0.65–15.01, p = 0.154) ( 43 ).…”
Section: Risk Factors For Aki In Ich Patientsmentioning
confidence: 99%
See 1 more Smart Citation